2020
DOI: 10.3201/eid2609.201524
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of N95 Respirator Decontamination and Reuse against SARS-CoV-2 Virus

Abstract: The coronavirus pandemic has created worldwide shortages of N95 respirators. We analyzed 4 decontamination methods for effectiveness in deactivating severe acute respiratory syndrome coronavirus 2 virus and effect on respirator function. Our results indicate that N95 respirators can be decontaminated and reused, but the integrity of respirator fit and seal must be maintained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
343
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(376 citation statements)
references
References 7 publications
21
343
3
5
Order By: Relevance
“…Six peer-reviewed studies and one non-peer-reviewed study have examined the viability of SARS-CoV-2 ( Table 3 ). Virus viability was assessed on a number of different materials, including glass [ 33 , 36 , 37 ], metal [ 27 , 36 , 37 , 38 , 39 , 40 ], plastic [ 27 , 37 , 38 , 40 ], paper [ 37 ], cardboard [ 27 ], rubber [ 38 , 40 ], wood, and cloth [ 37 ] ( Table 3 ). As observed for SARS-CoV-1, there was marked variation in the viability of SARS-CoV-2 across different types of materials ( Table 3 ).…”
Section: Virus Viabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Six peer-reviewed studies and one non-peer-reviewed study have examined the viability of SARS-CoV-2 ( Table 3 ). Virus viability was assessed on a number of different materials, including glass [ 33 , 36 , 37 ], metal [ 27 , 36 , 37 , 38 , 39 , 40 ], plastic [ 27 , 37 , 38 , 40 ], paper [ 37 ], cardboard [ 27 ], rubber [ 38 , 40 ], wood, and cloth [ 37 ] ( Table 3 ). As observed for SARS-CoV-1, there was marked variation in the viability of SARS-CoV-2 across different types of materials ( Table 3 ).…”
Section: Virus Viabilitymentioning
confidence: 99%
“…Importantly, some studies have determined the viability of SARS-CoV-2 directly on PPE or PPE-derived materials, including FFRs [ 37 , 38 , 39 , 40 ] ( Table 3 ). Fischer et al [ 39 ] reported a ~4.0 log 10 reduction of SARS-CoV-2 on N95 FFR disks after 24 h but, according to Chin et al [ 37 ], it took 7 days to achieve ~4.8 log 10 and ~3.0 log 10 reductions in SARS-CoV-2 infectivity on the inner and outer layers of surgical masks, respectively ( Table 3 ). Notably, while yet to be peer reviewed, the study by Kasloff et al [ 40 ] assessed SARS-CoV-2 viability using a soil load of mucin, bovine serum albumin, and tryptone as the inoculum, said to represent typical infectious body fluids of infected patients.…”
Section: Virus Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Different filter treatments as microwave-generated steam, warm moist heat and ultraviolet germicidal irradiation at 254 nm were able to determine a >4-log reduction of virus concentration in samples of facepiece respirators inoculated with H1N1 influenza virus. In 93% of cases, the virus was reduced to undetectable levels (13).…”
Section: Discussionmentioning
confidence: 99%
“…These contamination cycles caused light drops in filtration performance; however, the reduction of filtration performance revealed with this method is lower than that observed by a 70% ethanol sterilization cycle leading to alterations of filter structure. The decontamination process carried out with UV rays, on the other hand, did not result in any significant structural alterations of the filter (13).…”
Section: Introductionmentioning
confidence: 85%